The Effect of Board Characteristic and Ownership Structure on Corporate Social Responsibility of Indonesian Banking - Navyanti Nailil Muna; Henny Setyo Lestari (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to examine the influence of board characteristics and ownership structure on Corporate Social Responsibility (CSR). The study uses secondary data in the form of financial and annual reports from banking companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2023. The variables in this study are CSR as the dependent variable, women on board, board size, board meetings, ownership concentration, and managerial ownership as independent variables, and liquidity, firm age, profitability, and Capital Adequacy Ratio (CAR) as control variables. The sample was selected based on specific criteria, resulting in 34 companies from the banking industry. The data analysis used for hypothesis testing was panel data regression with E-Views 9 software. The results show that board size, liquidity, and firm age have a significant negative effect on CSR. Ownership concentration and profitability have a significant positive effect on CSR. Meanwhile, women on board, board meetings, managerial ownership, and CAR do not show any significant effect on CSR. The implication of this research is that to improve CSR performance, management needs to pay attention to board size, ownership concentration, liquidity, firm size, and profitability.